2023
DOI: 10.1038/s41556-022-01064-x
|View full text |Cite
|
Sign up to set email alerts
|

A topographic atlas defines developmental origins of cell heterogeneity in the human embryonic lung

Abstract: The lung contains numerous specialized cell types with distinct roles in tissue function and integrity. To clarify the origins and mechanisms generating cell heterogeneity, we created a comprehensive topographic atlas of early human lung development. Here we report 83 cell states and several spatially resolved developmental trajectories and predict cell interactions within defined tissue niches. We integrated single-cell RNA sequencing and spatially resolved transcriptomics into a web-based, open platform for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 142 publications
7
31
0
Order By: Relevance
“…Integrated UMAP overlay of our dataset (in red, Fig. 1F) with the published two datasets by He et al 9 , and Sountoulidis et al 10 , (combined, in grey) showed that 51 of the 58 cell clusters (~88%) were common amongst all three datasets (Fig. 1G and Extended Data Fig.…”
Section: Identification Of At Least 58 Distinct Cell Types In the Dev...mentioning
confidence: 52%
See 2 more Smart Citations
“…Integrated UMAP overlay of our dataset (in red, Fig. 1F) with the published two datasets by He et al 9 , and Sountoulidis et al 10 , (combined, in grey) showed that 51 of the 58 cell clusters (~88%) were common amongst all three datasets (Fig. 1G and Extended Data Fig.…”
Section: Identification Of At Least 58 Distinct Cell Types In the Dev...mentioning
confidence: 52%
“…Moreover, due to the technical difficulties of accurately discerning "proximal" versus "distal" airways, our data could not resolve regional differences between proximal vs distal specific cell types, as has previously been shown 9 . Despite these technical differences, our data unbiasedly captured many of the cell types/states and developmental trajectories previously observed in recent datasets 9,10,33 . Finally, while our data aimed to prevent over-clustering by using Clustree to identify the optimal resolution for sub-clustering, it is possible that this method may not have resolved finer differences in cell states resulting in lower cell types/states identified.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The rich diversity of cell origins in early lung development suggests the orchestration of different cell types from three germ layers upon organogenesis and proximal–distal patterning. Recently, human lung cell atlases from pseudoglandular to saccular stages were characterized at single-cell resolution 8 , 9 , 15 , 16 (Supplementary information, Fig. S1a ).…”
Section: Discussionmentioning
confidence: 99%
“…While our findings emphasize the importance of Zfhx3 as a mediator of CO 2 effects on AMØs, we also demonstrate expression of Zfhx3 mRNA and protein in alveolar epithelial cells (Supplemental Figure 1B and 1D). Moreover, single-cell RNA sequencing documents Zfhx3 expression in a broad array of cell types during human lung development 37 , and specifically in AMØs, alveolar epithelial cells, ciliated and mucus-secreting airway epithelial cells, fibroblasts, smooth muscle cells, adventitial cells and others in adult mouse and human lungs 38,39 . Widespread expression among many, but not all, cell types during development and in the adult lung suggests that Zfhx3 has multiple functions, as would be expected for such a large and complex protein.…”
Section: Discussionmentioning
confidence: 99%